Preparation and Application of Multi-Walled Carbon Nanotube-Supported Metconazole Suspension Concentrate for Seed Coating to Control Wheat Sharp Eyespot - Xuexiang Ren; Dongdong Qi; Zhao Li; Yu Chi; Xianyan Su; Kaixin Gu; Zhenghe Ye; Shun He; Li Chen (Agronomy, 2024)
Wheat sharp eyespot is a prevalent soil-borne disease that causes substantial economic losses in agriculture. Metconazole, a new triazole broad-spectrum fungicide, has demonstrated effective control of soil-borne diseases. Multi-walled carbon nanotubes (MWCNTs) are an innovative adsorbent material known for their large surface area and high absorptive capacity. This study identifies MWCNTs as the optimal adsorption material for metconazole, achieving an adsorption rate of 85.27% under optimal conditions (stirring time of 30 min and feeding ratio of 6:1). The optimized formula consists of 1.5% dispersant sodium wood, 1% emulsifier BY-112, 2% AEO-15, 3% glycol, 3% filmogen, and 4% red dyes. A 0.5% MWCNT–metconazole suspension concentrate for seed coating (FSC) significantly enhances the inhibitory effect of metconazole on wheat growth and promotes root development. At the tillering stage, a coating ratio of 1:100 shows a marked impact on wheat growth, and MWCNTs can improve the control effect of metconazole to Rhizoctonia cerealis. This work offers a novel approach for applying metconazole in a wheat suspension concentrate for seed coating.